An Analysis of Students’ Difficulties in Understanding English Vocabulary for The Mining Industry at State Vocational High School - Ummi Kalsum; Hariadi Syam; Nasmah Riyani; Karimuddin; Rais Abin; Susi Astiantih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The increasing demand for vocational graduates in the mining sector requires mastery of technical English vocabulary. However, research investigating students’ specific difficulties with mining-related English vocabulary at the vocational level remains limited. This study addresses that gap by exploring the types and causes of students’ difficulties in understanding mining-related English vocabulary at SMKN 2 Pomalaa. Employing a qualitative phenomenological approach, data were collected from five tenth-grade Heavy Equipment Engineering students through semi-structured interviews, classroom observation, and field notes, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that students struggle with pronunciation, remembering, understanding, and using technical vocabulary because the vocabulary is unfamiliar, highly technical, and rarely used in daily communication. Internal factors include limited vocabulary knowledge, low confidence, and low motivation, while external factors include limited learning resources, lack of exposure to technical English, and minimal opportunities to practice English outside the classroom. Theoretically, this study highlights the need for contextualized English for Specific Purposes (ESP) materials in vocational education to better support students’ readiness for employment in the mining industry.